QUALITY EVALUATION OF PASTA PRODUCED FROM WHEAT (Tricuma estivum), ACHA (Digitari aexilis), AND FLUTED PUMPKIN LEAF (Talfaera occidantalis) COMPOSITE FLOUR (FUDMA JOURNAL OF SCIENCES, 2025)
Pasta is one of the staple foods of developing countries, usually produced using unleavened durum wheat flour dough. This research evaluated the pasta quality produced from wheat, acha, and fluted pumpkin leaf composite flour. The pasta was made from combinations of acha, wheat, and fluted pumpkin leaf at 100 90:10:0, 85:10:5, and 80:10:10, respectively. The pasta was analyzed for proximate composition, mineral, physical, anti-nutrient, and sensory properties, and this was carried out on the samples with standard methods. The pasta's moisture, protein, fiber, and ash contents ranged from 6.63-13.23 %, 0.92-1.59 %, 7.66-12.02 %, and 7.97-13.78 %, respectively. Sodium, calcium, and magnesium ranged from 30.56-37.24%, 45.58-25.68%, and 208.8-260.5%, respectively. Tannin, phytate, and cyanide ranged from 256.25-287.50%, 196.80-220.80%, and 70.52-75.36%, respectively. Diameter, length, and weight ranged from 0.51-0.53 %, 20.50-23.50 %, and 84.50-91.29 %, respectively. The sensory ratings for aroma, taste, and texture ranged from 6.90-7.60, 6.85-7.55, and 6.95-7.80, respectively. The use of wheat, acha, and fluted pumpkin leaf composite flour in pasta production generally improved their protein, fat, fibre, and ash contents and aids in producing pasta of acceptable qualities from all ratios, However, pasta produced from 100% wheat flour was more acceptable in the sensory characteristics examined.
Keywords: Cereal food; Extruded food; Fluted pumpkin leaf; Fortified pasta; Pasta Products